(untitled) (Acta Polytechnica CTU Proceedings, 2016)
The magnitude and the spatial distribution of wind-induced net pressures (external and internal) on buildings are frequently discussed among research communities and construction industries. This paper deals with this topic based on a case study about an industrial building in Denmark, which was damaged due to the wind impact during a storm when a large part of the roof covering was blown off. In order to detect the reason for the damage the wind-induced loads were studied by i) wind tunnel experiments on the external pressures due to different wind directions, ii) analytical investigations of internal pressure due to envelope porosities and planned openings and iii) numerical analyses for the internal and the external pressure. The Reynolds averaged Navier-Stokes (RANS) method is employed to build a numerical model. The experimental, analytical and numerical results are compared with the indicated characteristic loads from the Eurocode.